2015
DOI: 10.1080/01932691.2014.921626
|View full text |Cite
|
Sign up to set email alerts
|

Surface and Antimicrobial Properties ofN-Palmitoyl Amino Acid–Based Surfactants

Abstract: Synthesized sodium N-pamitoyl amino acids were evaluated for surface and antimicrobial properties and compared with sodium lauryl sulphate (SLS). Emulsion stability of the amino acid surfactants and calcium tolerance of the sodium N-palmitoyl isoleucine were better as compared to SLS. Wetting ability and foaming properties of the palmitic acidbased surfactants were inferior to SLS. N-Acyl amino acids exhibited better antibacterial activity compared to sodium salts of N-acyl amino acids and standard compounds a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 28 publications
(34 reference statements)
0
13
0
Order By: Relevance
“…The emulsion stability of proline-based surfactants is as follows: SNAPro KNAPro PNAPro HNAPro CNAPro. The emulsion stability of mixture of sodium N-acyl prolines was superior as compared to pure individual fatty acyl prolines 30-213 s 2,19 . The emulsion stability decreased with an increase in the polarity of the amino acid head group from isoleucine to proline due to lower hydrophobicity 24 .…”
Section: Emulsion Stabilitymentioning
confidence: 94%
See 2 more Smart Citations
“…The emulsion stability of proline-based surfactants is as follows: SNAPro KNAPro PNAPro HNAPro CNAPro. The emulsion stability of mixture of sodium N-acyl prolines was superior as compared to pure individual fatty acyl prolines 30-213 s 2,19 . The emulsion stability decreased with an increase in the polarity of the amino acid head group from isoleucine to proline due to lower hydrophobicity 24 .…”
Section: Emulsion Stabilitymentioning
confidence: 94%
“…Calcium tolerance of mixture of sodium N-acyl prolines except CNAPro was found to be superior as compared to pure sodium N-oleoyl proline 75.9 ppm 17 , sodium N-palmitoyl proline 2.5 ppm 19 , and was inferior to N-lauroyl proline 1000 ppm 2 .…”
Section: Calcium Tolerancementioning
confidence: 96%
See 1 more Smart Citation
“…Besides, compositions based on amphiphiles with amino acid fragments exhibit controlled morphological [31] and rheological [32] behavior, valuable in oil recovery processes, for antimicrobial activity and suitable biodegradability [33]. Alongside with these reports, there are systematic investigations of the role of amino acid structures in various properties: it has been shown that variation of the structure of amino acid (proline, phenylalanine, isoleucine) could be used as a tool for regulating of the stability of emulsions based on them and antibacterial activity against Staphylococcus aureus and Bacillus subtilis strains [34]. Amphiphiles bearing polar amino acids and polar acidic amino acids (negatively charged) have attracted less attention.…”
Section: Amphiphilic Compounds Bearing Amino Acid Fragmentsmentioning
confidence: 99%
“…Although the two applications of AOS and OP-10 also presented the better film strength that showed relatively bigger foam diameter, their foaming volume was lesser. K12 and LAS, being excellent foaming monomers in distilled water, are easily effected by alkaline environment [24,25], so the synergistic effect of two mixtures is bad in the Ca(OH) 2 solution. Therefore, 1231 was chosen as the suds booster of the air entraining formula.…”
Section: Role and Selection Of Suds Boostermentioning
confidence: 99%